Global Knowledge Structure and Research Fronts of Kaempferol in Antidiabetic Studies: A Bibliometric and Science Mapping Analysis - Fathimah Fathimah; Katrin Roosita; Budi Setiawan; Zuraidah Nasution; Mohamad Rafi (Journal of Health and Nutrition Research, 2026)
Kaempferol, a widely distributed natural flavonoid, is increasingly studied for its antidiabetic properties. However, a comprehensive bibliometric analysis mapping the global research landscape of this field is currently lacking. This study aims to map research trends, collaborations, and the thematic evolution of kaempferol in diabetes-related studies from 2000 to 2025, while identifying emerging hotspots such as nutrigenomics and metabolomics. A total of 700 scientific documents were retrieved from the Scopus database. Bibliometric indicators and science mapping techniques—utilizing VOSviewer and Biblioshiny (RStudio)—were employed to analyze keyword co-occurrence networks, thematic evolution, and research dynamics. The field demonstrated a 19.5% average annual growth rate, encompassing 265 journals and 4,089 authors, reflecting a highly collaborative global environment. Thematic evolution revealed a distinct shift from early foundational studies on antioxidant activity and enzyme inhibition toward current research emphasizing molecular docking, gene modulation, and metabolic profiling. Recently, nutrigenomics and metabolomics have emerged as prominent focus areas. This bibliometric analysis provides a quantitative overview of the research landscape surrounding kaempferol and diabetes. The findings highlight an ongoing transition toward integrative, omics-based strategies, offering a structured foundation to guide future mechanistic and translational investigations.